------------------------------------------------------------------------
-- Weak bisimilarity
------------------------------------------------------------------------

{-# OPTIONS --without-K --safe #-}

module Delay-monad.Weak-bisimilarity {a} {A : Set a} where

open import Equality.Propositional
open import Logical-equivalence using (_⇔_)
open import Prelude

open import Bijection equality-with-J using (_↔_)
open import Double-negation equality-with-J
open import Function-universe equality-with-J hiding (id; _∘_)
open import H-level equality-with-J
open import H-level.Closure equality-with-J

using ([_]_∼_; [_]_∼′_; _∼_; now; later; force)

-- Weak bisimilarity, defined using mixed induction and coinduction.

infix 4 [_]_≈_ [_]_≈′_ _≈_ _≈′_

mutual

data [_]_≈_ (i : Size) : (x y : Delay A )  Set a where
now    :  {x}  [ i ] now x  now x
later  :  {x y}
[ i ] force x ≈′ force y
[ i ] later x   later y
laterˡ :  {x y}
[ i ] force x  y
[ i ] later x  y
laterʳ :  {x y}
[ i ] x  force y
[ i ] x  later y

record [_]_≈′_ (i : Size) (x y : Delay A ) : Set a where
coinductive
field
force : {j : Size< i}  [ j ] x  y

open [_]_≈′_ public

_≈_ : Delay A   Delay A   Set a
_≈_ = [  ]_≈_

_≈′_ : Delay A   Delay A   Set a
_≈′_ = [  ]_≈′_

-- Strong bisimilarity is contained in weak bisimilarity.

∼→≈ :  {i x y}  [ i ] x  y  [ i ] x  y
∼→≈ now       = now
∼→≈ (later p) = later λ { .force  ∼→≈ (force p) }

-- Termination predicates.

Terminates : Size  Delay A   A  Set a
Terminates i x y = [ i ] now y  x

infix 4 _⇓_

_⇓_ : Delay A   A  Set a
_⇓_ = Terminates

-- Terminates i is pointwise isomorphic to Terminates ∞.
--
-- Note that Terminates carves out an "inductive fragment" of [_]_≈_:
-- the only "coinductive" constructor, later, does not target
-- Terminates.

Terminates↔⇓ :  {i x y}  Terminates i x y  x  y
Terminates↔⇓ = record
{ surjection = record
{ logical-equivalence = record
{ to   = to
; from = from _
}
; right-inverse-of = to∘from
}
; left-inverse-of = from∘to
}
where
to :  {i x y}  Terminates i x y  x  y
to now        = now
to (laterʳ p) = laterʳ (to p)

from :  i {x y}  x  y  Terminates i x y
from _ now        = now
from _ (laterʳ p) = laterʳ (from _ p)

to∘from :  {i x y} (p : x  y)  to (from i p)  p
to∘from now        = refl
to∘from (laterʳ p) = cong laterʳ (to∘from p)

from∘to :  {i x y} (p : Terminates i x y)  from i (to p)  p
from∘to now        = refl
from∘to (laterʳ p) = cong laterʳ (from∘to p)

-- The computation now x is not weakly bisimilar to never.

now≉never :  {i x}  ¬ [ i ] now x  never
now≉never (laterʳ p) = now≉never p

-- Sometimes one can remove later constructors.

laterʳ⁻¹ :  {i} {j : Size< i} {x y}
[ i ] x  later y
[ j ] x  force y
laterʳ⁻¹ (later  p) = laterˡ (force p)
laterʳ⁻¹ (laterʳ p) = p
laterʳ⁻¹ (laterˡ p) = laterˡ (laterʳ⁻¹ p)

laterˡ⁻¹ :  {i} {j : Size< i} {x y}
[ i ] later x  y
[ j ] force x  y
laterˡ⁻¹ (later  p) = laterʳ (force p)
laterˡ⁻¹ (laterʳ p) = laterʳ (laterˡ⁻¹ p)
laterˡ⁻¹ (laterˡ p) = p

later⁻¹ :  {i} {j : Size< i} {x y}
[ i ] later x  later y
[ j ] force x  force y
later⁻¹ (later  p) = force p
later⁻¹ (laterʳ p) = laterˡ⁻¹ p
later⁻¹ (laterˡ p) = laterʳ⁻¹ p

-- Weak bisimilarity is reflexive.

reflexive :  {i} (x : Delay A )  [ i ] x  x
reflexive (now   x) = now
reflexive (later x) = later λ { .force  reflexive (force x) }

-- Weak bisimilarity is symmetric.

symmetric :  {i} {x y : Delay A }
[ i ] x  y
[ i ] y  x
symmetric now        = now
symmetric (later  p) = later λ { .force  symmetric (force p) }
symmetric (laterˡ p) = laterʳ (symmetric p)
symmetric (laterʳ p) = laterˡ (symmetric p)

-- The termination relation respects weak bisimilarity.
--
-- This function cannot be made size-preserving in its second argument
-- (unless A is uninhabited), see below.

⇓-respects-≈ :  {i} {x y : Delay A } {z}
Terminates i x z  x  y  Terminates i y z
⇓-respects-≈ now        now        = now
⇓-respects-≈ (laterʳ p) q          = ⇓-respects-≈ p (laterˡ⁻¹ q)
⇓-respects-≈ p          (laterʳ q) = laterʳ (⇓-respects-≈ p q)

-- Weak bisimilarity is transitive.

transitive-now :  {i x} {y z : Delay A }
[ i ] now x  y  y  z  [ i ] now x  z
transitive-now = ⇓-respects-≈

mutual

transitive-later :  {i x} {y z : Delay A }
later x  y  y  z  [ i ] later x  z
transitive-later p          (later  q) = later λ { .force
transitive (later⁻¹ p) (force q) }
transitive-later p          (laterʳ q) = later λ { .force
transitive (laterˡ⁻¹ p) q }
transitive-later p          (laterˡ q) = transitive-later (laterʳ⁻¹ p) q
transitive-later (laterˡ p) q          = laterˡ (transitive p q)

transitive :  {i} {x y z : Delay A }
x  y  y  z  [ i ] x  z
transitive {x = now   x} p q = transitive-now   p q
transitive {x = later x} p q = transitive-later p q

-- Some size-preserving variants of transitivity.
--
-- Many size-preserving variants cannot be defined (unless A is
-- uninhabited), see below.

transitive-∼≈ :
{i} {x y z : Delay A }
x  y  [ i ] y  z  [ i ] x  z
transitive-∼≈ now       q          = q
transitive-∼≈ (later p) (later  q) = later λ { .force
transitive-∼≈ (force p) (force q) }
transitive-∼≈ (later p) (laterˡ q) = laterˡ (transitive-∼≈ (force p) q)
transitive-∼≈ p         (laterʳ q) = laterʳ (transitive-∼≈ p q)

transitive-≈∼ :
{i} {x y z : Delay A }
[ i ] x  y  y  z  [ i ] x  z
transitive-≈∼ p q =
symmetric (transitive-∼≈ (S.symmetric q) (symmetric p))

-- Some equational reasoning combinators.

infix  -1 finally-≈ _∎≈
infixr -2 _≈⟨_⟩_ _≈⟨_⟩∼_ _≈⟨_⟩′∼_ _≈⟨⟩_ _∼⟨_⟩≈_ _≡⟨_⟩≈_ _≡⟨_⟩′≈_ _≳⟨⟩_

_∎≈ :  {i} (x : Delay A )  [ i ] x  x
_∎≈ = reflexive

_≈⟨_⟩_ :  (x : Delay A ) {y z}
x  y  y  z  x  z
_ ≈⟨ p  q = transitive p q

_≈⟨_⟩∼_ :  {i} (x : Delay A ) {y z}
[ i ] x  y  y  z  [ i ] x  z
_ ≈⟨ p ⟩∼ q = transitive-≈∼ p q

_≈⟨_⟩′∼_ :  {i} (x : Delay A ) {y z}
[ i ] x ≈′ y  y  z  [ i ] x ≈′ z
force (_ ≈⟨ p ⟩′∼ q) = transitive-≈∼ (force p) q

_≈⟨⟩_ :  {i} (x : Delay A ) {y}
[ i ] x  y  [ i ] x  y
_ ≈⟨⟩ p = p

_∼⟨_⟩≈_ :  {i} (x : Delay A ) {y z}
x  y  [ i ] y  z  [ i ] x  z
_ ∼⟨ p ⟩≈ q = transitive-∼≈ p q

_≡⟨_⟩≈_ :  {i} (x : Delay A ) {y z}
x  y  [ i ] y  z  [ i ] x  z
_≡⟨_⟩≈_ {i} _ p q = subst ([ i ]_≈ _) (sym p) q

_≡⟨_⟩′≈_ :  {i} (x : Delay A ) {y z}
x  y  [ i ] y ≈′ z  [ i ] x ≈′ z
force (_ ≡⟨ p ⟩′≈ q) = _ ≡⟨ p ⟩≈ force q

_≳⟨⟩_ :  {i} (x : Delay A ) {y}
[ i ] drop-later x  y  [ i ] x  y
now x   ≳⟨⟩ p = p
later x ≳⟨⟩ p = laterˡ p

finally-≈ :  {i} (x y : Delay A )
[ i ] x  y  [ i ] x  y
finally-≈ _ _ p = p

syntax finally-≈ x y p = x ≈⟨ p ⟩∎ y ∎

-- The following size-preserving variant of laterʳ⁻¹ and laterˡ⁻¹ can
-- be defined.
--
-- Several other variants cannot be defined (unless A is uninhabited),
-- see below.

laterˡʳ⁻¹ :
{i} {x y : Delay′ A }
[ i ] later x  force y
[ i ] force x  later y
[ i ] force x  force y
laterˡʳ⁻¹ {i} p q = laterˡʳ⁻¹′ p q refl refl
where
laterˡʳ⁻¹″ :
{x′ y′} {x y : Delay′ A }
({j : Size< i}  [ j ] x′  force y)
({j : Size< i}  [ j ] force x  y′)
later x  x′  later y  y′
[ i ] later x  later y
laterˡʳ⁻¹″ p q refl refl = later λ { .force  laterˡʳ⁻¹ p q }

laterˡʳ⁻¹′ :
{x′ y′} {x y : Delay′ A }
[ i ] later x  y′
[ i ] x′  later y
x′  force x  y′  force y
[ i ] x′  y′
laterˡʳ⁻¹′ (later  p) (later  q) x′≡  y′≡  = laterˡʳ⁻¹″ (force p)                (force q)                x′≡ y′≡
laterˡʳ⁻¹′ (laterʳ p) (later  q) x′≡  y′≡  = laterˡʳ⁻¹″  { {_}  laterˡ⁻¹ p }) (force q)                x′≡ y′≡
laterˡʳ⁻¹′ (later  p) (laterˡ q) x′≡  y′≡  = laterˡʳ⁻¹″ (force p)                 { {_}  laterʳ⁻¹ q }) x′≡ y′≡
laterˡʳ⁻¹′ (laterʳ p) (laterˡ q) x′≡  y′≡  = laterˡʳ⁻¹″  { {_}  laterˡ⁻¹ p })  { {_}  laterʳ⁻¹ q }) x′≡ y′≡
laterˡʳ⁻¹′ (laterˡ p) _          refl refl = p
laterˡʳ⁻¹′ _          (laterʳ q) refl y′≡  = subst ([ i ] _ ≈_) (sym y′≡) q

-- If a computation does not terminate, then it is weakly bisimilar
-- to never.

¬⇓→⇑ :  {i} x  ¬ ( λ y  x  y)  [ i ] never  x
¬⇓→⇑ (now   x) ¬⇓ = ⊥-elim (¬⇓ (_ , now))
¬⇓→⇑ (later x) ¬⇓ = later λ { .force  ¬⇓→⇑ _ (¬⇓  Σ-map id laterʳ) }

-- In the double-negation monad every computation is weakly
-- bisimilar to either never or now something.

¬¬[⇑⊎⇓] :  x  ¬¬ (never  x   λ y  x  y)
¬¬[⇑⊎⇓] x = [ inj₂ , inj₁  ¬⇓→⇑ _ ] ⟨\$⟩ excluded-middle

-- The notion of weak bisimilarity defined here is not necessarily
-- propositional.

¬-≈-proposition : ¬ (∀ {x y}  Is-proposition (x  y))
¬-≈-proposition =
(∀ {x y}  Is-proposition (x  y))  ↝⟨  prop  _⇔_.to propositional⇔irrelevant (prop {x = never} {y = never}))
Proof-irrelevant (never  never)    ↝⟨  irr  irr _ _)
proof₁  proof₂                     ↝⟨  ()) ⟩□
⊥₀
where
proof₁ : never  never
proof₁ = later λ { .force  proof₁ }

proof₂ : never  never
proof₂ = laterˡ proof₁

-- However, if A is a set, then the termination predicate is
-- propositional.

Terminates-propositional :
Is-set A   {i x y}  Is-proposition (Terminates i x y)
Terminates-propositional A-set {i} =
_⇔_.from propositional⇔irrelevant  p q  irr p q refl)
where
irr :
{x y y′}
(p : [ i ] now y   x)
(q : [ i ] now y′  x)
(y≡y′ : y  y′)
subst (([ i ]_≈ x)  now) y≡y′ p  q
irr         (laterʳ p) (laterʳ q) refl = cong laterʳ (irr p q refl)
irr {y = y} now        now        y≡y  =
subst (([ i ]_≈ now y)  now) y≡y  now  ≡⟨ cong  eq  subst _ eq _) (_⇔_.to set⇔UIP A-set y≡y refl)
subst (([ i ]_≈ now y)  now) refl now  ≡⟨⟩
now

-- If x terminates with y and z, then y is equal to z.

termination-value-unique :
{i x y z}  Terminates i x y  Terminates i x z  y  z
termination-value-unique now        now        = refl
termination-value-unique (laterʳ p) (laterʳ q) =
termination-value-unique p q

-- If A is a set, then ∃ λ y → x ⇓ y is propositional.

∃-Terminates-propositional :
Is-set A   {i x}  Is-proposition ( (Terminates i x))
∃-Terminates-propositional A-set =
_⇔_.from propositional⇔irrelevant λ where
(y₁ , x⇓y₁) (y₂ , x⇓y₂)
Σ-≡,≡→≡
(termination-value-unique x⇓y₁ x⇓y₂)
(_⇔_.to propositional⇔irrelevant
(Terminates-propositional A-set) _ _)

------------------------------------------------------------------------
-- Alternative definitions of weak bisimilarity

-- An alternative definition of weak bisimilarity (basically the one
-- used in the paper "Partiality, Revisited: The Partiality Monad as a
-- Quotient Inductive-Inductive Type" by Altenkirch, Danielsson and
-- Kraus).
--
-- This definition is pointwise logically equivalent to the one above,

infix 4 _≈₂_

_≈₂_ : Delay A   Delay A   Set a
x ≈₂ y =  z  x  z  y  z

-- If A is a set, then this alternative definition of weak
-- bisimilarity is propositional (assuming extensionality).

≈₂-propositional :
Extensionality a a
Is-set A   {x y}  Is-proposition (x ≈₂ y)
≈₂-propositional ext A-set =
Π-closure ext 1 λ _
⇔-closure ext 1 (Terminates-propositional A-set)
(Terminates-propositional A-set)

-- Another alternative definition of weak bisimilarity, basically the
-- one given by Capretta in "General Recursion via Coinductive Types".

infix 4 [_]_≈₃_ [_]_≈₃′_ _≈₃_

mutual

data [_]_≈₃_ (i : Size) : Delay A   Delay A   Set a where
both-terminate :  {x y v}  x  v  y  v  [ i ] x ≈₃ y
later          :  {x y}
[ i ] force x ≈₃′ force y
[ i ] later x ≈₃  later y

record [_]_≈₃′_ (i : Size) (x y : Delay A ) : Set a where
coinductive
field
force : {j : Size< i}  [ j ] x ≈₃ y

open [_]_≈₃′_ public

_≈₃_ : Delay A   Delay A   Set a
_≈₃_ = [  ]_≈₃_

-- If A is inhabited, then this definition is not propositional.

¬-≈₃-propositional : A  ¬ (∀ {x y}  Is-proposition (x ≈₃ y))
¬-≈₃-propositional x =
(∀ {x y}  Is-proposition (x ≈₃ y))  ↝⟨  prop  prop)
Is-proposition (y ≈₃ y)              ↝⟨ _⇔_.to propositional⇔irrelevant
Proof-irrelevant (y ≈₃ y)            ↝⟨ (_\$ _)  (_\$ _)
proof₁  proof₂                      ↝⟨  ()) ⟩□

where
y : Delay A
y = later λ { .force  now x }

proof₁ : y ≈₃ y
proof₁ = both-terminate (laterʳ now) (laterʳ now)

proof₂ : y ≈₃ y
proof₂ = later λ { .force  both-terminate now now }

-- The last definition of weak bisimilarity given above is pointwise
-- logically equivalent to the first one. Note that the proof is
-- size-preserving.
--
-- (Given suitable notions of extensionality the two definitions are
-- not pointwise isomorphic, because given such assumptions there is
-- only one proof of never ≈₃ never, but multiple proofs of
-- never ≈ never. However, there is no Agda proof of this claim in
-- this module.)

≈⇔≈₃ :  {i x y}  [ i ] x  y  [ i ] x ≈₃ y
≈⇔≈₃ = record { to = to; from = from }
where
mutual

laterˡ′ :  {i x x′ y}
x′  force x
[ i ] x′      ≈₃ y
[ i ] later x ≈₃ y
laterˡ′ eq (both-terminate x⇓ y⇓) = both-terminate
(laterʳ (subst (_⇓ _) eq x⇓))
y⇓
laterˡ′ eq (later p)              = later (laterˡ″ eq p)

laterˡ″ :  {i x x′ y}
later x′  x
[ i ] force x′ ≈₃′ y
[ i ] x        ≈₃′ y
force (laterˡ″ refl p) = laterˡ′ refl (force p)

mutual

laterʳ′ :  {i x y y′}
y′  force y
[ i ] x ≈₃ y′
[ i ] x ≈₃ later y
laterʳ′ eq (both-terminate x⇓ y⇓) = both-terminate
x⇓
(laterʳ (subst (_⇓ _) eq y⇓))
laterʳ′ eq (later p)              = later (laterʳ″ eq p)

laterʳ″ :  {i x y y′}
later y′  y
[ i ] x ≈₃′ force y′
[ i ] x ≈₃′ y
force (laterʳ″ refl p) = laterʳ′ refl (force p)

to :  {i x y}  [ i ] x  y  [ i ] x ≈₃ y
to now        = both-terminate now now
to (later  p) = later λ { .force  to (force p) }
to (laterˡ p) = laterˡ′ refl (to p)
to (laterʳ p) = laterʳ′ refl (to p)

from⇓ :  {i x y v}  x  v  y  v  [ i ] x  y
from⇓ now        now        = now
from⇓ p          (laterʳ q) = laterʳ (from⇓ p q)
from⇓ (laterʳ p) q          = laterˡ (from⇓ p q)

from :  {i x y}  [ i ] x ≈₃ y  [ i ] x  y
from (both-terminate x⇓v y⇓v) = from⇓ x⇓v y⇓v
from (later p)                = later λ { .force  from (force p) }

------------------------------------------------------------------------
-- Lemmas stating that certain size-preserving functions can be
-- defined iff A is uninhabited

-- A lemma used in several of the proofs below: If A is uninhabited,
-- then weak bisimilarity is trivial.

uninhabited→trivial :  {i}  ¬ A   x y  [ i ] x  y
uninhabited→trivial ¬A (now   x) _         = ⊥-elim (¬A x)
uninhabited→trivial ¬A (later x) (now   y) = ⊥-elim (¬A y)
uninhabited→trivial ¬A (later x) (later y) =
later λ { .force  uninhabited→trivial ¬A (force x) (force y) }

-- A variant of laterˡ⁻¹ in which one occurrence of weak bisimilarity
-- is replaced by strong bisimilarity, and both arguments are
-- specialised, can be made size-preserving iff A is uninhabited.
--
-- This lemma is used to prove all similar results below (directly or
-- indirectly), with the exception that an alternative, more direct
-- proof is also given for one of the results.

Laterˡ⁻¹-∼≈ =  {i} {x : A}
[ i ] later  { .force  now x })  never
[ i ] now x                         never

size-preserving-laterˡ⁻¹-∼≈⇔uninhabited : Laterˡ⁻¹-∼≈  ¬ A
size-preserving-laterˡ⁻¹-∼≈⇔uninhabited = record
{ to   = Laterˡ⁻¹-∼≈  ↝⟨  laterˡ⁻¹-∼≈ x  contradiction (laterˡ⁻¹-∼≈ {_}) x ) ⟩□
¬ A
; from = ¬ A              ↝⟨ uninhabited→trivial
(∀ x y  x  y)  ↝⟨  trivial {_ _} _  trivial _ _) ⟩□
Laterˡ⁻¹-∼≈
}
where

module _ (laterˡ⁻¹-∼≈ : Laterˡ⁻¹-∼≈) (x : A) where

mutual

now≈never :  {i}  [ i ] now x  never
now≈never = laterˡ⁻¹-∼≈ (later now∼never)

now∼never :  {i}  [ i ] now x ∼′ never
force now∼never {j = j} = ⊥-elim (contradiction j)

contradiction i = now≉never (now≈never {i = i})

-- A variant of Laterˡ⁻¹-∼≈ which it is sometimes easier to work with.

Laterˡ⁻¹-∼≈′ =  {i} {x : A}
[ i ] later (record { force = now x })  never
[ i ] now x                             never

size-preserving-laterˡ⁻¹-∼≈′⇔uninhabited : Laterˡ⁻¹-∼≈′  ¬ A
size-preserving-laterˡ⁻¹-∼≈′⇔uninhabited =
Laterˡ⁻¹-∼≈′  ↝⟨ record { to   = _∘ S.transitive (later λ { .force  now })
; from = _∘ S.transitive (later λ { .force  now })
}
Laterˡ⁻¹-∼≈   ↝⟨ size-preserving-laterˡ⁻¹-∼≈⇔uninhabited ⟩□
¬ A

-- A variant of laterʳ⁻¹ in which one occurrence of weak bisimilarity
-- is replaced by strong bisimilarity, and both arguments are
-- specialised, can be made size-preserving iff A is uninhabited.

Laterʳ⁻¹-∼≈ =  {i x}
[ i ] never  later (record { force = now x })
[ i ] never  now x

size-preserving-laterʳ⁻¹-∼≈⇔uninhabited : Laterʳ⁻¹-∼≈  ¬ A
size-preserving-laterʳ⁻¹-∼≈⇔uninhabited =
Laterʳ⁻¹-∼≈   ↝⟨ record { to   = λ laterʳ⁻¹  symmetric  laterʳ⁻¹  S.symmetric
; from = λ laterˡ⁻¹  symmetric  laterˡ⁻¹  S.symmetric
}
Laterˡ⁻¹-∼≈′  ↝⟨ size-preserving-laterˡ⁻¹-∼≈′⇔uninhabited ⟩□
¬ A

-- The function laterˡ⁻¹ can be made size-preserving iff A is
-- uninhabited.

Laterˡ⁻¹ =  {i x y}
[ i ] later x  y
[ i ] force x  y

size-preserving-laterˡ⁻¹⇔uninhabited : Laterˡ⁻¹  ¬ A
size-preserving-laterˡ⁻¹⇔uninhabited = record
{ to   = Laterˡ⁻¹     ↝⟨ _∘ ∼→≈
Laterˡ⁻¹-∼≈  ↝⟨ _⇔_.to size-preserving-laterˡ⁻¹-∼≈⇔uninhabited ⟩□
¬ A
; from = ¬ A              ↝⟨ uninhabited→trivial
(∀ x y  x  y)  ↝⟨  trivial {_ _ _} _  trivial _ _) ⟩□
Laterˡ⁻¹
}

-- The function laterʳ⁻¹ can be made size-preserving iff A is
-- uninhabited.

Laterʳ⁻¹ =  {i x y}
[ i ] x  later y
[ i ] x  force y

size-preserving-laterʳ⁻¹⇔uninhabited : Laterʳ⁻¹  ¬ A
size-preserving-laterʳ⁻¹⇔uninhabited =
Laterʳ⁻¹  ↝⟨ record { to   = λ laterʳ⁻¹  symmetric  laterʳ⁻¹  symmetric
; from = λ laterˡ⁻¹  symmetric  laterˡ⁻¹  symmetric
}
Laterˡ⁻¹  ↝⟨ size-preserving-laterˡ⁻¹⇔uninhabited ⟩□

¬ A

-- A variant of ⇓-respects-≈ in which _≈_ is replaced by _∼_ can be
-- made size-preserving in the second argument iff A is uninhabited.

⇓-Respects-∼ʳ =  {i} {x y : Delay A } {z}
x  z  [ i ] x  y  Terminates i y z

size-preserving-⇓-respects-∼ʳ⇔uninhabited : ⇓-Respects-∼ʳ  ¬ A
size-preserving-⇓-respects-∼ʳ⇔uninhabited = record
{ to   = ⇓-Respects-∼ʳ  ↝⟨  resp  resp (laterʳ now))
Laterˡ⁻¹-∼≈    ↝⟨ _⇔_.to size-preserving-laterˡ⁻¹-∼≈⇔uninhabited
¬ A
; from = ¬ A              ↝⟨ uninhabited→trivial
(∀ x y  x  y)  ↝⟨  trivial {_ _ _ _} _ _  trivial _ _) ⟩□
⇓-Respects-∼ʳ
}

-- The lemma ⇓-respects-≈ can be made size-preserving in the second
-- argument iff A is uninhabited.

⇓-Respects-≈ʳ =  {i} {x y : Delay A } {z}
x  z  [ i ] x  y  Terminates i y z

size-preserving-⇓-respects-≈ʳ⇔uninhabited : ⇓-Respects-≈ʳ  ¬ A
size-preserving-⇓-respects-≈ʳ⇔uninhabited = record
{ to   = ⇓-Respects-≈ʳ  ↝⟨  resp x⇓z  resp x⇓z  ∼→≈)
⇓-Respects-∼ʳ  ↝⟨ _⇔_.to size-preserving-⇓-respects-∼ʳ⇔uninhabited ⟩□
¬ A
; from = ¬ A              ↝⟨ uninhabited→trivial
(∀ x y  x  y)  ↝⟨  trivial {_ _ _ _} _ _  trivial _ _) ⟩□
⇓-Respects-≈ʳ
}

-- There is a variant of transitivity-≈∼ that preserves the size of
-- the second argument iff A is uninhabited.

Transitivity-≈∼ʳ =  {i} {x y z : Delay A }
x  y  [ i ] y  z  [ i ] x  z

size-preserving-transitivity-≈∼ʳ⇔uninhabited : Transitivity-≈∼ʳ  ¬ A
size-preserving-transitivity-≈∼ʳ⇔uninhabited = record
{ to   = Transitivity-≈∼ʳ  ↝⟨  trans  trans)
⇓-Respects-∼ʳ     ↝⟨ _⇔_.to size-preserving-⇓-respects-∼ʳ⇔uninhabited ⟩□
¬ A
; from = ¬ A               ↝⟨ uninhabited→trivial
(∀ x y  x  y)   ↝⟨  trivial {_ _ _ _} _ _  trivial _ _) ⟩□
Transitivity-≈∼ʳ
}

-- There is a variant of transitivity-∼≈ that preserves the size of
-- the first argument iff A is uninhabited.

Transitivity-∼≈ˡ =  {i} {x y z : Delay A }
[ i ] x  y  y  z  [ i ] x  z

size-preserving-transitivity-∼≈ˡ⇔uninhabited : Transitivity-∼≈ˡ  ¬ A
size-preserving-transitivity-∼≈ˡ⇔uninhabited =
Transitivity-∼≈ˡ  ↝⟨ record { to   = λ trans {_ _ _ _} p q
symmetric (trans (S.symmetric q) (symmetric p))
; from = λ trans {_ _ _ _} p q
symmetric (trans (symmetric q) (S.symmetric p))
}
Transitivity-≈∼ʳ  ↝⟨ size-preserving-transitivity-≈∼ʳ⇔uninhabited ⟩□

¬ A

-- There is a transitivity proof that preserves the size of the
-- second argument iff A is uninhabited.

Transitivityʳ =  {i} {x y z : Delay A }
x  y  [ i ] y  z  [ i ] x  z

size-preserving-transitivityʳ⇔uninhabited : Transitivityʳ  ¬ A
size-preserving-transitivityʳ⇔uninhabited = record
{ to   = Transitivityʳ  ↝⟨  trans  trans)
⇓-Respects-≈ʳ  ↝⟨ _⇔_.to size-preserving-⇓-respects-≈ʳ⇔uninhabited ⟩□
¬ A
; from = ¬ A              ↝⟨ uninhabited→trivial
(∀ x y  x  y)  ↝⟨  trivial {_ _ _ _} _ _  trivial _ _) ⟩□
Transitivityʳ
}

-- There is a transitivity proof that preserves the size of the
-- first argument iff A is uninhabited.

Transitivityˡ =  {i} {x y z : Delay A }
[ i ] x  y  y  z  [ i ] x  z

size-preserving-transitivityˡ⇔uninhabited : Transitivityˡ  ¬ A
size-preserving-transitivityˡ⇔uninhabited =
Transitivityˡ  ↝⟨ record { to   = λ trans {_ _ _ _} p q
symmetric (trans (symmetric q) (symmetric p))
; from = λ trans {_ _ _ _} p q
symmetric (trans (symmetric q) (symmetric p))
}
Transitivityʳ  ↝⟨ size-preserving-transitivityʳ⇔uninhabited ⟩□

¬ A

-- There is a fully size-preserving variant of transitivity iff A is
-- uninhabited.

Transitivity =  {i} {x y z : Delay A }
[ i ] x  y  [ i ] y  z  [ i ] x  z

size-preserving-transitivity⇔uninhabited : Transitivity  ¬ A
size-preserving-transitivity⇔uninhabited = record
{ to   = Transitivity   ↝⟨  trans  trans)
Transitivityˡ  ↝⟨ _⇔_.to size-preserving-transitivityˡ⇔uninhabited
¬ A
; from = ¬ A              ↝⟨ uninhabited→trivial
(∀ x y  x  y)  ↝⟨  trivial {_ _ _ _} _ _  trivial _ _) ⟩□
Transitivity
}

-- The following two lemmas provide an alternative proof of one
-- direction of the previous lemma (with a small change to one of the
-- types).

-- If there is a transitivity proof that is size-preserving in both
-- arguments, then weak bisimilarity is trivial.

size-preserving-transitivity→trivial :
(∀ {i} x {y z : Delay A }  [ i ] x  y  [ i ] y  z  [ i ] x  z)
{i} (x y : Delay A )  [ i ] x  y
size-preserving-transitivity→trivial _≈⟨_⟩_ x y =
(x                         ≈⟨ laterʳ (x ∎ʷ)
(later  { .force  x })  ≈⟨ later  { .force  size-preserving-transitivity→trivial _≈⟨_⟩_ x y })
(later  { .force  y })  ≈⟨ laterˡ (y ∎ʷ)
(y                         ∎ʷ))))
where
_∎ʷ = reflexive

-- If there is a transitivity proof that is size-preserving in both
-- arguments, then the carrier type A is not inhabited.

size-preserving-transitivity→uninhabited :
(∀ {i} x {y z : Delay A }
[ i ] x  y  [ i ] y  z  [ i ] x  z)
¬ A
size-preserving-transitivity→uninhabited trans x =
now≉never (size-preserving-transitivity→trivial trans (now x) never)